ЖАДИДЧИЛИК ДАВРИДА ИККИ ТИЛЛИ ТАРЖИМА ЛУҒАТЛАРИ ВА УЛАРНИНГ ТАКОМИЛЛАШУВ ЖАРАЁНИ - Нормаматов, С. (SCIENCE and SOCIETY, 2019)
The author of the article scientifically analyzes the general lexicographical features of the Jadid-era bilingual translation dictionaries and the process of improving the principles of their compilation in the examples of glossaries created by Ashurali Zahiri and Abdulla Qodiriy.